Republic of Latvia : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2014)
Latvia entered the euro area in January 2014 with the fastest rate of growth in Europe. The 2014 Article IV Consultation highlights that a slowdown in investment and exports was partly compensated by robust consumption demand, supported by rising real wages, bringing GDP growth in 2013 to 4.1 percent. Strong job creation reduced the unemployment rate to 11.3 percent by end-2013, close to its structural level. Consumer price inflation fell to an average of about zero in 2013, mainly owing to weakening energy prices. The 2013 general government deficit outturn of 1.0 percent of GDP was below the target of 1.4 percent.